Characteristics of the Sectoral Qualifications Framework Levels for the EU Member States Border Guards Training in Academic Education - Andrii Balendr (Pedagogical Discourse, 2017)
In this article the author gives characteristics for the Sectoral Qualifications Framework (SQF) levels of the European Union (EU) Member States border guards training. The main role of this framework is to act as a means of coordination for national qualifications, ensuring comparability of qualifications and curricula. This should facilitate mobility and development of exchange programmes for the officers of border guard organizations, with the goal of providing common EU approaches to the organization of border security and introduction of common border guard standards across the EU. The SQF analysed in the article is a set of defined qualifications, with all the training achievements limited by the certain sector of education. The SQF for border guards includes also the criteria for determining the number of credits and quality assurance and a comprehensive structure. The SQF for Border Guards elaborated by the EU border protection agency FRONTEX comprises 5 training cycles, such as: Generic Border Guard Training; Border Control; Cross Border Investigations and Intelligence; Supervising, Management, Leadership; Specialist Fields Border Guarding (optional), which, in their turn, are divided into knowledge, skills and competencies. It has been also analyzed the experience of the leading EU border guard organisations with the purpose of introducing it into the training system of the State Border Guard Service of Ukraine. The author indicates that the system of training of the personnel of the State Border Guard Service of Ukraine requires such an instrument for development and classification of qualifications and that presupposes further study of the border guard’s training system of the EU countries.Key words: training of border guards, Sectoral Qualifications Framework, qualification levels, academic education, European Union countries.